In Quest of Ores from Bohemia to the End of the World: How a Geologist sees the World - POŠMOURNÝ, Karel (GeoScience Engineering, 2020)
In Quest of Ores from Bohemia to the End of the World is the name of a new book by Petr Láznička, a leading Czech-Canadian-Australian geologist, published in Czech this year. Professor Petr Láznička (Peter Laznicka) is a globally renowned expert in the field of ore deposits and metallogenesis. Similar publications on the world’s ore deposits in Czech are rare. We can state that the work of Professor Petr Láznička is in a way exceptional. During his 65-year career, he became a recognized authority in the fields of deposit geology and metallogenesis. Unfortunately, he has become more recognized abroad than in the Czech Republic. This book is the first comprehensive publication in Czech about Láznička’s life and work. At the same time, it is also an expression of honours to his merits in the scientific and economic knowledge of ore deposits and his approach to this complex issue. The book was published by the Czech Geological Survey in Prague in 2020, ISBN: 978-80-7075-994-3. It has 393 pages and costs CZK 450. DOI 10.35180/gse-2020-0041